Systematic studies of Philippine Rubus L. (Rosaceae) - Real, Mark Stephen B. (Animo Repository, 2019)
The classification and relationships of Philippine Rubus species were determined after the examination of morphology and molecular data from different collected specimens of Rubus species in the country. Cluster analysis and principal component analysis of morphological data from Rubus species show that plant habit and leaf characters, which include the number of leaflets, leaf division, and leaf blade margins, are important basis in delimiting taxa at infrageneric level, while further examination of morphological characters among select group of Rubus species show that floral characters, which include the pubescence of the hypanthium and sepals, shape of the petals, sepal division, type of inflorescence, and sexuality of the individual flowers, are necessary to delimit the organisms at the species level. Analysis of chloroplast DNA support this observation. A total of 22 species are recognized, at least eight species of which are endemic. It is proposed that Rubus tagallus Cham et Schlechtend and R. elmeri Focke are resurrected as species, and further studies are recommended to delimit the R. moluccanus L. complex at the variety level.